Defective DNA damage repair leads to frequent catastrophic genomic events in murine and human tumors. Issue 1 (December 2018) - Ratnaparkhe, Manasi; Wong, John; Wei, Pei-Chi; Hlevnjak, Mario; Kolb, Thorsten; Simovic, Milena; Haag, Daniel; Paul, Yashna; Devens, Frauke; Northcott, Paul; Jones, David; Kool, Marcel; et al.
Abstract Chromothripsis and chromoanasynthesis are catastrophic events leading to clustered genomic rearrangements. Whole-genome sequencing revealed frequent complex genomic rearrangements (n = 16/26) in brain tumors developing in mice deficient for factors involved in homologous-recombination-repair or non-homologous-end-joining. Catastrophic events were tightly linked toMyc/Mycn amplification, with increased DNA damage and inefficient apoptotic response already observable at early postnatal stages. Inhibition of repair processes and comparison of the mouse tumors with human medulloblastomas (n = 68) and glioblastomas (n = 32) identified chromothripsis as associated withMYC/MYCN gains and with DNA repair deficiencies, pointing towards therapeutic opportunities to target DNA repair defects in tumors with complex genomic rearrangements. Chromothripsis and chromoanasynthesis lead to locally clustered rearrangements affecting one or a few chromosomes, but their impact on cancer development and progression is unclear. Here the authors analyse the role of DNA repair factors in brain tumors by whole-genome sequencing of tumors from mouse models of medulloblastoma or high grade gliomas.